GDP : A Brief but Affectionate History - Coyle, Diane (Princeton : Princeton University Press, 2015)
Why did the size of the U.S. economy increase by 3 percent on one day in mid-2013 - or Ghana's balloon by 60 percent overnight in 2010? Why did the U.K. financial industry show its fastest expansion ever at the end of 2008 - just as the world's financial system went into meltdown? This title deals with these questions.
From the eighteen century to the 1930s: war and depression -- 1945 to 1975: the golden age -- The legacy of the 1970s: a crisis of capitalism -- 1995 to 2005: the new paradigm -- Our times: the Great Crash -- The future: twenty-first century GDP.
Includes bibliographical references (page 149-159) and index.
Keywords: Gross domestic product -- History; Economic history; Economics -- History; Econometrics -- History; Econometrics; Economic history; Economics; Gross domestic product; History